MODEL PEMBELAJARA NUMBERED HEAD TOGETHER(NHT) UNTUK MATERI POKOK RELASI DAN FUNGSI PADA SISWA KELAS VIII SMPN 1 BAJAWA - Agustina Dhiu (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2019)
The problem faced by students in SMPN 1 Bajawa Utara is the lack of student participation in the teaching and learning process because teachers tend to use conventional learning methods, so students do not have the opportunity to think or express opinions either individually or in groups. To overcome these problems, the teacher must choose an appropriate learning method. One of them is cooperative learning type Numbered Heads Together (NHT). Because NHT type of cooperative learning focuses more on student cooperation in small groups of 3 - 5 people and divided heterogeneously. This type of research is experimental research with a quantitative approach. Sources of data from student learning outcomes tests are pre-test and post-test. The population was all eighth grade students of SMP Negeri 1 Bajawa Utara, samples taken were 10 students using simple random sampling technique. Data were analyzed with descriptive analysis and covariance analysis (ANAKOVA) techniques. The preparation of the NHT model of learning tools carried out produces good learning tools because they meet the requirements of validity, reliability, and sensitivity. The results of covariance analysis obtained statistics F count = 20.29035 and F table = 4.45 with the numerator dk = 1 and the denominator d = 17, giving a significant value (F arithmetic> F table). This shows that the NHT model gives effective results.